How to fail at almost everything and still win big : kind of the story of my life - Adams, Scott, 1957- (Portfolio/Penguin, 2013)
"Dilbert creator Scott Adams offers his most personal book ever -- a funny memoir of his many failures and what they eventually taught him about success. How do you go from hapless office worker to world-famous cartoonist and bestselling author in just a few years? No career guide can answer that, and not even Scott Adams (who actually did it) can give you a road map that works for everyone. But there's a lot to learn from his personal story, and a lot of humor along the way. In How to Fail at Almost Everything and Still Win Big, Adams admits that he failed at just about everything he's tried, including his corporate career, his inventions, his investments, and his two restaurants. But along the way, Adams discovered some truths you're unlikely to find anywhere else. "--